2020
DOI: 10.14393/bj-v36n4a2020-41955
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characteristics and productivity of tomato plants in function of nitrogen sources and doses

Abstract: The objective of this study was to evaluate the effect of nitrogen sources and rates on the physicochemical characteristics and yield of tomato plants. Forty hybrids were cultivated at 100 and 400 kg ha-1 of N, combined with four sources (urea, ammonium sulfate, ammonium nitrate and calcium), plus a treatment without N application in a randomized complete block design four replicates. Size, stem diameter, number of leaves, SPAD (Soil Plant Analysis Development), leaf nitrogen, number of fruits / plants, fruit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Overall, there were very small effects of the reduced N supply on tomato fruit yield and quality. Even the N content of the fruits (Table 4) was not affected by the N supply, in the same way as the other mineral elements (Table 4), which is in accordance with other studies with a comparable or even more severe N reduction than in our experiment [26,29,40,42,[53][54][55]. As proposed by Stefanelli et al [3], reduced N contents in plants would be expected if the N supply to plants was low.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, there were very small effects of the reduced N supply on tomato fruit yield and quality. Even the N content of the fruits (Table 4) was not affected by the N supply, in the same way as the other mineral elements (Table 4), which is in accordance with other studies with a comparable or even more severe N reduction than in our experiment [26,29,40,42,[53][54][55]. As proposed by Stefanelli et al [3], reduced N contents in plants would be expected if the N supply to plants was low.…”
Section: Discussionsupporting
confidence: 93%
“…As proposed by Stefanelli et al [3], reduced N contents in plants would be expected if the N supply to plants was low. However, the N content of the tomato leaves was not affected by the reduced N supply (data not shown), similarly to other reports of the N content in plants [40,53,54,56]. In other studies, there were no impacts of low N fertilizer levels on photosynthetic activity [57,58] and very little effects on the height and the aboveground biomass [27,40,53,56] of soil-grown tomato plants.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These authors suggest that fertilization practices using NO 3 − and NH 4 + are recommended in order to improve quality. Assunção et al [20] found an increase in • Brix and the longitudinal diameter of fruits as a function of the N dose. The objective of this research was the improvement of fertilizer use efficiency in greenhouse areas in the Mediterranean region, through the assessment of the effect of several fertigation strategies based on the reduction of the total nitrogen applied, as well as on the use of a percentage of NH 4 + as a nitrogen source, on the decrease in the environmental impacts caused by the traditional system, and if they are compatible with a high fruit yield (quantity and quality).…”
Section: Introductionmentioning
confidence: 95%